Cordyceps militaris polysaccharide alleviates diabetic symptoms by regulating gut microbiota against TLR4/NF-κB pathway - Zhao, Huajie; Li, Min; Liu, Liang; Li, Duan; Zhao, Linjing; Wu, Zhen; Zhou, Mingxu; Jia, Le; Yang, Fan (International journal of biological macromolecules, 2023)
The relationship between gut microbiota and type 2 diabetes mellitus (T2DM) has attracted increasing attention. In our work, one purified fraction a (AEPSa) was obtained from Cordyceps militaris polysaccharides, and its hypoglycemic activity and underlying mechanisms were investigated in high-fat diet (HFD)- and streptozotocin (STZ)-induced T2DM mice. The results revealed that AEPSa reshaped gut microbiota by increasing Allobaculum, Alistipes, Lachnospiraceae_NK4A136_group and norank_f_Muribaculaceae and decreasing Enterococcus and Ruminococcus_torques_group to inhibit the colonic toll-like receptor 4 (TLR4)/nuclear factor kappa-B (NF-κB) pathway and upregulate intestinal tight junction protein expression, thereby improving glucose and serum lipid metabolism, hormone secretion and complications. Fecal microbiota transplantation (FMT) also confirmed these findings. These results indicated that symptomatic relief of T2DM might be related to AEPSa regulating the gut microbiota against the TLR4/NF-κB pathway to protect the intestinal barrier. Therefore, AEPSa might be developed as a prebiotic agent against T2DM by regulating gut microbiota. •One purified fraction a (AEPSa) was obtained from C. militaris polysaccharides.•AEPSa obviously altered the composition and diversity of gut flora in T2DM mice.•AEPSa protected gut barrier by inhibiting TLR4/NF-κB pathway in T2DM mice.•AEPSa might be developed as prebiotic agents against T2DM by regulating gut flora.